The third dimension of alpine plant leaf traits is related to cold-tolerance - Yuan Wang; Ji Suonan; Kun Liu; Yanni Gao; Sihao Zhu; Qian Liu; Ning Zhao (Plant Diversity)
Alpine plants possess unique traits to adapt alpine environments. Whether leaf trait relationships of alpine plants can be captured by the two trait dimensions of organ size and resource economics is unknown. We hypothesized that, beyond the trait dimensions of leaf size and resource economics, non-structured carbohydrates (NSC) would reflect a dimension of cold-tolerance in alpine plants. To test this hypothesis, we measured 12 leaf traits critical to leaf construction and growth in 143 species across 7 sites ranging from alpine steppes to alpine meadows along an environmental gradient on the Tibetan Plateau. Furthermore, a cold resistance experiment was conducted at one of these sites to estimate the lethal temperature causing 50% frost damage (LT50) of 11 alpine species. The majority of variations in 12 leaf traits of alpine plants were captured by three trait axes, in which leaf carbon (LCC) and NSC (including leaf starch; LSC and leaf soluble sugars; LSS) were clustered in a new dimension (PC3) beyond leaf size and structure, and resource economics. Although LCC, LSC and LSS all showed negative correlations with mean annual temperature, a significant negative correlation was only found between LSS and LT50. It indicated that PC3 was able to reflect the cold-tolerance of alpine plants to some extent, in which LSS was the most critical trait. The storage and transformation of NSC under stressful conditions could reflect a dimension of long-term metabolic adaptation and cold-tolerance, which is an extension of the resource-utilization strategy beyond construction cost and growth.